THE CORRELATION OF OVERBITE WITH SKELETAL, DENTAL AND SOFT TISSUES CHARACTERISTICS - Zafar ul Islam; Attiya Shaikh; Mubassar Fida (Pakistan Oral & Dental Journal, 2020)
The objective was to determine correlation of the dental, skeletal and soft tissue characteristics with overbite and gender dimorphism. Lateral cephalographs were traced manually for 170 subjects who comprised of 80 males and 90 females. The subjects were divided into three groups based on the amount of overbite recorded on the subject’s dental models. Various angles and measurements representing the dental, skeletal and soft tissue parameters were recorded. The data were analyzed using SPSS version 20.0 for windows. Multivariate analysis of covariance and Pearson’s correlation were applied to determine the difference and correlation of various skeletal, dental and soft tissues among the three overbite groups and gender of the subjects. A p value of ≤0.05 was taken to be statistically significant. Statistically significant difference was seen for the parameters like MxIH (p = .003), MxMH (p = .05), MnIH (p = .001) and MnMH (p = .001), angle ANB (p = .006), angle SNMP (p = .001), angle FMA (p = .001) and AFHR (p = .001), lip length (p = .003) and incisor stomion (p = .001) across the overbite groups. A negative weak but significant correlation was seen for FMA, SNMP, AFHR, MxMH, MnMH and lip length with overbite. The incisor stomion and ANB showed positive weak but significant correlation with the overbite. The study concluded that skeletal characteristics are significantly increased in open bite group as compared to deep bite and normal overbite. The maxillary and mandibular molars showed increased heights in the open bite group. The deep bite subjects indicated significantly decreased lip length as compared to normal overbite. The incisor stomion was significantly increased in deep bite group. All the values are significantly greater in males than females.